Upaya Guru Kelas dalam Meningkatkan Pemahaman Materi IPA di MI - Kurniawati, Yohana; Ambarwati, Ambarwati (Sekolah Tinggi Agama Islam Pati, 2024)
AbstractThis study aims to describe the efforts of classroom teachers in improving understanding of Natural science subject in MI. This type of research is field research with a qualitative approach. Data collection methods used observation, interviews, documentation. Data sources from the headmaster, class teacher, subject matter teacher, and students at MI Khoiriyah Pati. Data analysis with data reduction, display, and verification. The results showed that the teacher tried to improve the understanding of the material by providing orientation, apperception, and evaluation to students. The obstacles in improving students' understanding of science are inadequate school facilities, teacher abilities, classroom atmosphere and conditions, and student willingness. Meanwhile, efforts to overcome obstacles, namely teachers strive to use existing media/ facilities at school, attend workshops, provide motivation for students who do not understand the material, use interesting methods, strategies, approaches that are in accordance with students' understanding abilities, and conduct creative innovative learning to increase student interest in learning. The conclusion of the research is the efforts made by teachers by providing apperception, orientation, and evaluation. The obstacles faced are facilities, teacher abilities, classroom atmosphere, and student motivation. Efforts made are using existing facilities at school, attending workshops, innovating innovatively creatively in learning. The impact of the research is that student understanding has increased.